2005
DOI: 10.1080/08912960500284729
|View full text |Cite
|
Sign up to set email alerts
|

A Jurassic amber deposit in Southern Thailand

Abstract: International audiencePublished reports of amber predating the Aptian are rare and mention only amber pieces the size of millimetric marbles. Mid Cretaceous amber records, however, show a dramatic increase in number as well as in the size of the pieces, a phenomenon which is still poorly understood. The discovery of the first Jurassic deposit with comparatively large centimetric sized pieces of amber, in southern Thailand, is significant. Taphonomy and palaeobotany indicate a dense forest surrounding a coastal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…In contrast, 16,17-bisnorsimonellite(16) and bisnorsimonellite(20) were found only in Albian−Cenomanian Charentese samples, and 12-hydroxysimonellite(29) was found only in the Cenomanian sample Fo. Other compounds belonging to the callitrisate and dehydroabietane families, methyl-15,16,17-trinordehydroabietate (21), methyl dehydroabietate (27), 16,17-bisnordehyroabietic acid (28), and methyl-15,16-dehydrocallitrisate (30), were identified in some samples but not detected in others (Table S2, Supporting Information).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, 16,17-bisnorsimonellite(16) and bisnorsimonellite(20) were found only in Albian−Cenomanian Charentese samples, and 12-hydroxysimonellite(29) was found only in the Cenomanian sample Fo. Other compounds belonging to the callitrisate and dehydroabietane families, methyl-15,16,17-trinordehydroabietate (21), methyl dehydroabietate (27), 16,17-bisnordehyroabietic acid (28), and methyl-15,16-dehydrocallitrisate (30), were identified in some samples but not detected in others (Table S2, Supporting Information).…”
mentioning
confidence: 66%
“…It could be derived from abietane precursors by diagenetic alteration, 54,55 so it has no chemosystematic importance. With the presence of 16,17-bisnorsimonellite (16), bisnorsimonellite (20), and 12-hydroxysimonellite (29), Pyrenean amber is more comparable to Charentese samples A1 and F1 (Table S2, Supporting Information), as well as to Spanish (Cantabrian) amber and the leaves of Frenelopsis. 53 This suggests a cheirolepidiaceous origin of Pyrenean amber, which is in accord with the associated plant remains (Table S1, Supporting Information).…”
Section: Journal Of Natural Productsmentioning
confidence: 85%
“…Azar et al (2010) reported the discovery of nine Late Jurassic amber outcrops in Lebanon making it the second record of Jurassic amber after Thailand (Philippe et al, 2005). Jurassic amber was found also in Daohugou (a single droplet) in the Middle Jurassic during the field trip occasioned by the Fifi;h FossilX3 Conference in China (Azar pers.…”
mentioning
confidence: 96%
“…Amber outcrops predating the Lower Cretaceous are scarce, and usually contain pieces of small millimetric sizes from Jurassic, Triassic and Carboniferous ages (GianoUa et al, 1998;Philippe et al, 2005;Roghi et al, 2006;Sargent Bray and Anderson, 2009;Azar et al, 2010;Schmidt et al, 2012).…”
mentioning
confidence: 98%
“…The Khlong Min Formation, which is probably Middle to Late Jurassic in age, has yielded a diverse vertebrate assemblage (Buffetaut et al 1994b) including sharks, bony fishes, temnospondyl amphibians, turtles, crocodiles and dinosaurs (Buffetaut et al 2005b). It also contains plant remains, including amber (Philippe et al 2005).…”
mentioning
confidence: 99%